Molecular analysis of multifocal prostate cancer cases - SABALIAUSKAITĖ, Rasa; PETROŠKA, Donatas; DASEVIČIUS, Darius; LAURINAVIČIUS, Arvydas; JANKEVIČIUS, Feliksas; LAZUTKA, Juozas R.; JARMALAITĖ, Sonata (Acta medica Lituanica, 2011)
Background. Prostate cancer (PCa) is usually a multifocal disease with different foci displaying histological and molecular heterogeneity. Biopsy-based pathology diagnosis of PCa may not be representative of the entire tumour; thus, markers more precisely characterizing every focus of multifocal PCa are highly instrumental for a better testing of PCa.Materials and Methods. Two distant foci of prostate adenocarcinoma were obtained from prostatectomy specimens of ten patients with pT2–pT3 stage PCa. The expression of TMPRSS2 : ERG, TMPRSS2 : ETV1, and TERT was assessed by means of reverse transcription PCR and quantified using the real-time-based approach. Ki-67, ERG, EMA, AMACR, p16, and p53 expression was evaluated by means of immunohistochemistry (IHC) on tissue microarrays (TMA).Results. Two out of ten cases were identified with different Gleason scores in paired foci of PCa. The expression of most of the IHC markers was quite even between TMA cores of each PCa case, with p16 showing the highest level of heterogeneity (44%; 4/9); 80% (8/10) of multifocal PCa expressed different variants of the TMPRSS2 : ERG transcript or showed a varying status of fusion positivity in paired foci, and the expression levels of the transcript were also heterogeneous. Similarly, 90% (9/10) of PCa showed a different positivity for TERT expression in paired foci.Conclusions. Measurement of TMPRSS2 : ERG and TERT expression offers a valuable tool for identifying most aggressive tumour foci and selecting a relevant treatment of PCa.Keywords: prostate cancer, multifocality, TMPRSS2 : ERG, telomerase